A case study on the special clothing needs of the elderly in relation to the concept of care and well-being - Capua, Joanna Mae M. (College of Home Economics, University of the Philippines Diliman, 2009)
This thesis research is a case study on the special clothing needs of the elderly in relation to the concept of care and well-being. It intended to identify the particular clothing needs of they elderly who were already dependent to caregivers, to document their daily activities in life and be able to distinguish distinct clothing needs which could lessen the dependence to caregivers. It also meant to find out what were the actions taken by caregivers to provide the elderly with clothing solutions that will answer the identified clothing needs like making dressing and undressing activity a lot easier, through evaluation of current wardrobe, activities of daily living and physical state of the elderly. The research attempted to find the psychosocial effect of dress to the elderly; if independence in grooming and dressing through the use of appropriate clothing construction, fabric, openings and closures, could help give the elderly self-esteem. The research method employed a descriptive method of research and purposive sampling as used to obtain information namely, a 79-year old female elderly and an 81-year old blind male elderly under the custody of a home caregiver. Instruments included interviews, ocular and participative observations with the elderly, family members and caregivers. Continence checklist and photo documentation were also used in data collection. Tables and charts were used to order and organize the data. Frequency and percentages summarized the results from the tables used. The following were the significant findings of the research on the clothing needs and clothing behavior of the elderly: a) The capacity of the elderly to carry on an independent and self-sufficient lifestyle wherein he could care for his personal needs like self-care continuously declines through time. Walking around, bathing/toileting (incontinence) and dressing (and undressing) were the most common problems of the elderly; b) Independence in clothing was a concern of the elderly; garments that have self-help features increased self-reliance and gave them more opportunity for lively involvement socially and interpersonally; c) The elderly have negative notions on the use of the diaper as a solution to incontinence problems. It made them feel incompetent; d) The family and the caregiver's concern to ease the process of dressing and undressing of the elderly were worked out with alterations in ready-to-wear garments and custom made clothing which comprises most of the wardrobe. Top factors considered choosing garments were ease of wearing, comfort and fit, and fabric; e)Clothing decisions on the wardrobe of the elderly were managed mainly by the caregiver. The study focused on the recognition of the clothing needs of the elderly. It gave recognition to the viewpoint of the caregivers in making the process of giving care and well-being for the elderly less difficult. The special needs of the elderly for clothing may also inspire manufacturers to develop garments to address unique requirements. The researchers had the following recommendations: a) Undertake more studies on clothing provisions and clothing problems of elderly under the care of institutions; b) Encourage manufacturing firms to cater to the special clothing needs of the elderly or handicapped; c) Provide further research to address, the special clothing concerns of the elderly such as, grment construction, fabric selection, type and location of fastenings among others.